The ‘New Asia’ and Academia: the Art of Crafting Shared Regional Spaces - Sondaite van Soest, Rima (Acta Orientalia Vilnensia, 2003)
This paper presents and evaluates strategies employed by Southeast Asian academics and think tanks in ‘regionalizing knowledge’. Sections one and two of the paper provide an overview of recent ‘Asian’ historical imaginings, arguing that the search for the “roots of ASEAN” in the distant past is politically motivated. The final two sections focus on an intellectual project involving some of the most prominent scholars of East and South Asia. Those involved in InterAsia, also known as the Movements project, are scholaractivists with a well-articulated political agenda. In analyzing the interAsian agenda, I question its implications: “decolonizing mindset” and “becoming Asian” are fraught with ambiguity.